2017
DOI: 10.1177/1044207317714747
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the 2010 VA PTSD Rule Change on Veterans’ Disability Compensation and Reported Cognitive Disability

Abstract: In July 2010, the Department of Veterans Affairs (VA) simplified the process of obtaining veterans' disability compensation (DC) for veterans with posttraumatic stress disorder (PTSD) who served in combat zones but not in combat roles. In this article, we use data from the Current Population Survey (CPS) Veterans Supplement to estimate the impacts of the change in the VA PTSD rule on DC benefit receipt and self-reported cognitive disability. We hypothesize that the easing of eligibility rules led to an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Table 1 shows benefit receipt statistics for the two matched groups. Contreary et al (2017) showed that receipt of DC increased after the 2010 rule change among veterans who had served in combat zones compared with those who had served in noncombat zones. To confirm that receipt of DC increased in our sample, we conducted a pre-post analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows benefit receipt statistics for the two matched groups. Contreary et al (2017) showed that receipt of DC increased after the 2010 rule change among veterans who had served in combat zones compared with those who had served in noncombat zones. To confirm that receipt of DC increased in our sample, we conducted a pre-post analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive disability. Following the approach used in Contreary et al (2017), we identified cognitive difficulty using a question from the U.S. Census Bureau’s six-question sequence on disability, which has been included in the CPS-ASEC since 2009: “Because of a physical, mental, or emotional condition, does [the subject] have serious difficulty concentrating, remembering, or making decisions?” We used this question as an imperfect proxy for PTSD—the term “cognitive difficulty” applies to a larger set of functional limitations than those often associated with PTSD.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Two changes in the later period could be considered a direct outgrowth of the recession: expansions in SNAP and Section 8 housing vouchers. A 2010 change in the Department of Veterans Affairs' (VA) eligibility for veterans' disability compensation due to posttraumatic stress disorder contributed to the growth in VA expenditures for disabled veterans and to the percentage of veterans reporting a disability (Contreary, Tennant, & Ben-Shalom, 2017). In addition, the expansion of Medicaid coverage in a majority of states to all working-age adults with household incomes below 138% of the federal poverty level, prompted by provisions of the Patient Protection and Affordable Care Act of 2010 (ACA), increased Medicaid enrollment and expenditures for working-age people with disabilities.…”
Section: Discussionmentioning
confidence: 99%